Effect of storage period and strain of layer on internal and external quality characteristics of eggs marketed in Riyadh area - A.A. Alsobayel; M.A. Albadry (Journal of the Saudi Society of Agricultural Sciences)
The study was undertaken to compare the effect of storage period on external and internal quality traits of brown and white shelled eggs produced by commercial layers and marketed in Riyadh area. Two trays each containing 30 eggs from each egg color were randomly collected from supermarket, three times at different time intervals. The eggs of each collection were randomly divided into three groups of 20 eggs. The different egg groups were individually weighed and stored in refrigerator for 0, 10 and 20 days at 7 °C and 60% relative humidity. Egg air cell depth (AC), shape index (SI) and specific gravity (SG) were measured for all of the eggs in each group. Blood (BS) and meat (MS) spots, Haugh unit values (HU), yolk color grade (C), shell weight (SW), shell thickness (ST), egg surface area (SA), shell density (SD) and shell weight per unit of egg surface area (SWUSA) of each individual eggs were measured. The results shows that white shell eggs had significantly higher weight, surface area and lower shape index and blood spot incidence. Storage period had a significant (P < .05) adverse effect upon Haugh unit values, specific gravity, air cell depth and shell thickness but a positive effect upon shell density and shell weight per unit of surface area of brown and white shelled eggs but Haugh unit values of white shelled eggs were more adversely affected by prolonged storage period. In conclusion, results showed that brown and white shelled eggs stored for 20 days at 7 °C and 60% relative humidity still maintain relatively good internal quality characteristics for human consumption.